ПРОБЛЕМНОЕ ОБУЧЕНИЕ - КАК ОДИН ИЗ ИННОВАЦИОННЫХ ТЕХНОЛОГИЙ ОБУЧЕНИЯ ИДИОМАТИЧЕСКИМ ВЫРАЖЕНИЯМ АНГЛИЙСКОГО ЯЗЫКА СТУДЕНТОВ ФИЛОЛОГОВ - Калабаева, М.А. (SCIENCE and SOCIETY, 2023)
Today the problem-based learning technology is actively used in solving a fairly wide range of issues of teaching foreign languages, although there is no experience of its use for the formation and improvement of idiomatic competence in the modern linguodidactic paradigm.
Keywords: technology; problem-based learning; cultural linguistics; idiomatic expressions